THE SYNTACTIC STRUCTURE OF AWGNI NOUN PHRASES - Agajie, Berhanu Asaye (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2020)
The objective of this study is to examine the syntactic structure of Awgni Noun Phrases. The assumption of Labeling Algorithm {XP, H} is holding on, and a descriptive research design was employed to explore the intended objective. Data for this research were enriched by interviewing 12 native speakers of Awgni specializing in the proposed language. Through expert samplings, 20 Noun Phrases were selected and illustrated. Results showed that the Noun Phrases in Awgni could be formed out of the head Nouns all along through other lexical categories reminiscent of the Noun Phrases, Adjective Phrases, Verb Phrases, Determiner Phrases, and Adverb Phrases.  These grammatical items were serving as dependents to the head Nouns. The head Nouns in Awgni are for all time right-headed. These heads are the only obligatory constituents, while the Phrasal categories are optional elements which could be either modifiers or complements to the head Nouns. In this regard, Labeling Algorithm explicitly chooses the contiguous Noun heads that are the label of the complete Syntactic Objects (SOs) anticipated for all Noun Phrase structures.